LEARNING STRATEGY TRAINING: FACTORS NEED CONSIDERING FOR THE IMPLEMENTATION IN EFL CONTEXT - Widiani Tresnaningsih (Premise: Journal of English Education and Applied Linguistics, 2012)
Learning strategies are defined as special thoughts, actions and behaviors taken in the purpose of achieving learning objectives. Many researches have found that applying learning strategies in English as a Foreign Language (EFL) context seem effective. As the extension, there is an attempt to train or to instruct the learning strategies in the purpose of building students’ awareness of the importance of applying strategies in their learning which is later on known as ‘learning strategy training’ or ‘learning strategy instruction’. This present article discusses some factors need considering for the implementation of learning strategy training in EFL context. The factors include: Principles of effective strategy training, selecting appropriate learning strategies, explicit or integrated strategy training, language of instruction, and strategy training models. The discussion emphasizes on the literature review available from many sources and the previous researches concerning on learning strategies and learning strategy training. Suggestions are also included for the strategy training implementation to provide the better and more effective one in the future.